Catalogue of construction products containing secondary raw materials from different industries and municipal waste - Tereza Pavlů; Jan Pešta; Martin Volf; Antonín Lupíšek (Acta Polytechnica CTU Proceedings, 2022)
The building industry consumes a large amount of primary raw materials and also contributes significantly to the production of waste. Applying circular principles in this field to reduce resource consumption and waste production has been investigated in several projects considering the reuse or recycling of construction and demolition waste. However, consumption of primary raw materials can also be reduced by re-targetting waste from different industries and municipal waste to produce new construction products. Thus, opportunities for the recycling of industrial and municipal waste were investigated in this project. The main output is the catalogue, which provides an overview of products with recycled content and secondary materials with the potential to be used in the construction industry such as blast furnace slag, ash, and energy by-products. Also, it contains a list of valid requirements for the use of recycled materials under specific conditions of the Czech Republic. In addition, examples of good practice are presented to break the existing behavioral barriers to the use of secondary raw materials in the Czech construction industry. This contribution summarizes the findings in the field of industrial and municipal waste recycling and its further use as secondary raw materials in the construction industry.